The mythical man-month : essays on software engineering - Brooks, Frederick P., Jr., 1931-2022 (Addison-Wesley Pub. Co., 1995)
These essays draw from Brooks' experience as project manager for the IBM System/360 computer family and then for OS/360, its massive software system. Now, 20 years after the initial publication of his book, Brooks has revisited his original ideas and added new thoughts and advice. -- from publisher description.